2020
DOI: 10.1002/mgg3.1416
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inhibitory factor (MIF) gene polymorphisms are associated with disease susceptibility and with circulating MIF levels in active non‐segmental vitiligo in patients from western Mexico

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 82 publications
3
15
0
Order By: Relevance
“…Farag and colleagues (2018) observed that the concentration of serum MIF was higher in subjects with vitiligo, constituting a possible biomarker of disease severity [31]. In another study with a larger patient cohort, similar observations were made regarding MIF levels, with the difference that MIF levels were also associated with patient treatment status [183]. The serum levels of granulocyte-macrophage colony-stimulating factor (GM-CSF), essential for the development of immune system stem cells, were also found increased in patients with vitiligo, indicating the role of these cells in vitiligo pathogenesis [30].…”
Section: Vitiligomentioning
confidence: 76%
“…Farag and colleagues (2018) observed that the concentration of serum MIF was higher in subjects with vitiligo, constituting a possible biomarker of disease severity [31]. In another study with a larger patient cohort, similar observations were made regarding MIF levels, with the difference that MIF levels were also associated with patient treatment status [183]. The serum levels of granulocyte-macrophage colony-stimulating factor (GM-CSF), essential for the development of immune system stem cells, were also found increased in patients with vitiligo, indicating the role of these cells in vitiligo pathogenesis [30].…”
Section: Vitiligomentioning
confidence: 76%
“… 26 Limited research, however, has looked into its function in the pathophysiology of dermatological disorders. 27 MIF has been thought to play a key function as a proinflammatory cytokine since its discovery; however, MIF is now thought to modulate the inflammatory “set point” by controlling the release of other pro-inflammatory mediators. 28 Glucocorticoids enhanced rather than suppressed MIF production, and this mechanism regulates inflammatory and immunological responses.…”
Section: Discussionmentioning
confidence: 99%
“…17 The minor MIF -173 C allele or the GC genotype has also been associated with other diseases such as rheumatoid arthritis, juvenile idiopathic arthritis, systemic sclerosis, systemic lupus erythematosus, vitiligo, and sarcoidosis. 12,19,[28][29][30][31] This association indicates that the MIF gene could be a common genetic marker of the autoimmune and inflammatory diseases of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using the OpenEpi v. 3.01 software considering 23.6% as the frequency of the minor allele at ‐173 G>C polymorphism according to previous reports in the Mexican population. 20 The patients were recruited from the Jalisco Dermatological Institute, "Dr. José Barba Rubio," of the Mexican Ministry of Health, Guadalajara, Jalisco, Mexico. In addition, 232 clinically healthy subjects were also included as controls, with no family relationship to the patients or a psoriasis history.…”
Section: Methodsmentioning
confidence: 99%